Research progress on the comprehensive utilization of pit bottom water of distiller's grains,a by-product of sauce-flavor Baijiu - YANG Wenjuan, WANG Xiaodan, JIANG Wen, CAO Wentao (Zhongguo niangzao)
Pit bottom water of distiller's grains, also known as Huangshui or Huangjiangshui, is a by-product of the brewing of sauce-flavor (Jiangxiangxing) Baijiu. The pit bottom water of distiller's grains is rich in organic components and microbial resources, and has the characteristics of low pH, high chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Direct discharge is easy to waste resources and pollute the environment. In recent years, improving the utilization rate of organic matter in pit bottom water and increasing its added value have become research hotspots. At present, the research on pit bottom water only focuses on strong-flavor (Nongxiangxing) and light-flavor (Qingxiangxing) Baijiu, while there are few research reports on the comprehensive utilization of pit bottom water of sauce-flavor Baijiu distiller's grains or the utilization rate is not high. In this paper, the physicochemical and microbial characteristics of pit bottom water of distiller's grains were summarized, the comprehensive utilization of pit bottom water was analyzed, and the treatment methods of pit bottom water were summarized, aiming to provide a theoretical basis for the rational utilization of pit bottom water resources, and have certain reference value in reducing environmental pollution and the cost of treatment of brewing by-products.